2011
DOI: 10.1186/1476-4598-10-33
|View full text |Cite
|
Sign up to set email alerts
|

Small-cell lung cancer-associated autoantibodies: potential applications to cancer diagnosis, early detection, and therapy

Abstract: Small-cell lung cancer (SCLC) is the most aggressive lung cancer subtype and lacks effective early detection methods and therapies. A number of rare paraneoplastic neurologic autoimmune diseases are strongly associated with SCLC. Most patients with such paraneoplastic syndromes harbor high titers of antibodies against neuronal proteins that are abnormally expressed in SCLC tumors. These autoantibodies may cross-react with the nervous system, possibly contributing to autoimmune disease development. Importantly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 184 publications
(226 reference statements)
1
53
0
1
Order By: Relevance
“…Immunologic processes causing autoantibody production are believed to be generated by the immune system in response to mutations, degradation, overexpression of proteins, and/or the release of proteins from damaged tissue (20)(21)(22)(23). Autoantibody production is also believed to be caused by mis-presentation or misfolding of proteins, which may be recognized by the immune system leading to autoantibody production and therefore, TAAs or proteins that have undergone alternate posttranslational modifications (PTM) may be recognized as nonautologous (17,19,24), that is, their phosphorylation, glycosylation, oxidation, or proteolytic cleavage could generate a neo-epitope or enhance self-epitope presentation and affinity to the MHC or T-cell receptor, inducing an immune response (25).…”
Section: Introductionmentioning
confidence: 99%
“…Immunologic processes causing autoantibody production are believed to be generated by the immune system in response to mutations, degradation, overexpression of proteins, and/or the release of proteins from damaged tissue (20)(21)(22)(23). Autoantibody production is also believed to be caused by mis-presentation or misfolding of proteins, which may be recognized by the immune system leading to autoantibody production and therefore, TAAs or proteins that have undergone alternate posttranslational modifications (PTM) may be recognized as nonautologous (17,19,24), that is, their phosphorylation, glycosylation, oxidation, or proteolytic cleavage could generate a neo-epitope or enhance self-epitope presentation and affinity to the MHC or T-cell receptor, inducing an immune response (25).…”
Section: Introductionmentioning
confidence: 99%
“…Database searches suggest that most of the PNS autoantigen genes contain the RE1 element (Supplementary Table S2). It was suggested that these antibodies have usage for early detection and diagnosis of SCLC (28). There is no information whether nSR100 affects the expression of PNS autoantigens, which contain the RE1 element.…”
Section: Vgcc Subunit A2d2 Is Regulated Through Re1 By Restmentioning
confidence: 99%
“…Anti-Hu antibodies were detected in the patient's serum at a low titre, which is a highly uncommon finding, as the patient also had Hashimoto's thyroiditis. Low antibody titres are usually present in SCLC patients without autoimmune diseases (25). Those with SCLC and no clinical PNS have detectable anti-Hu antibodies in their serum in ~16-25% of the cases (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Low antibody titres are usually present in SCLC patients without autoimmune diseases (25). Those with SCLC and no clinical PNS have detectable anti-Hu antibodies in their serum in ~16-25% of the cases (25)(26)(27). When SCLC and PNS are found concurrently, the latter is usually mediated by a high titre of anti-Hu antibodies (28).…”
Section: Discussionmentioning
confidence: 99%